Z Generation's Intention to Use Zakat Digital Payment: The Mediating Effect of Trust (UIN Sunan Kudus, 2022)
The goal of this study was to examine the variables that may affect Muslims in the Z generation's desire to make digital zakat payments. The UTAUT theory was employed in this study. PLS-SEM was used to analyze the data and test the hypothesis. 158 users of digital payment systems responded to the survey in total. The study's findings indicate that while performance expectancy has no impact on the intention to pay zakat through digital payments, effort expectancy, social influence, conducive conditions, and trust do. Additionally, trust promotes conditions and mediates social effects on behavioral intention, but it does not mediate performance expectations or effort expectations.